Hypersonic flows for reentry problems: proceedings of a workshop, held in Antibes, France, 22-25 January 1990 - Desideri, J.-A. (Jean-Antoine), 1951-; Periaux, Jacques; Glowinski, R. (Berlin ; Springer-Verlag, 1991)
Survey lectures and test cases for analysis v.1; Experiments and computations v.2